HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING - Raudana Aziah Nuha; Yoseph Pedhu (Universitas Katolik Indonesia Atma Jaya, 2021)
Emotional intelligence is an individual's ability to understand and feel the feelings of oneself and others which includes self-emotion recognition, emotional management, motivation, empathy, and social skills. Creative thinking ability is an individual's ability to find answers to problems appropriately and varied which has the characteristics of fluency, flexibility, originality, and elaboration. This study was conducted to determine the relationship between emotional intelligence and creative thinking skills of students of the Guidance and Counseling Study Program at Atma Jaya Catholic University of Indonesia. The subjects of this study were all students of the Guidance and Counseling Study Program class of 2019 and 2020. The research data was collected using a rating scale instrument. The results showed that there was a positive and significant relationship between emotional intelligence and creative thinking ability with a correlation coefficient of 0.781. Emotional intelligence contributes 61% to the ability to think creatively.